Effect of Vitamin D Supplementation on the Fetal Growth Rate in Pregnancy Complicated by Fetal Growth Restriction - Karolina Jakubiec-Wisniewska; Hubert Huras; Magdalena Kolak (Children, 2022)
Background: Fetal growth restriction (FGR) increases the risk of intrauterine fetal death, infant death and complications in childhood, and diseases that appear in adulthood. Vitamin D may affect fetal vascular flow. The aim of the study was to check if the rate of fetal growth in pregnant women with FGR differs depending on whether the patient was supplemented with vitamin D in the recommended dose of 2000 IU, not supplemented at all, or supplemented with vitamin D in low doses. Methods: Patients were divided into two groups: suboptimal vitamin D dosage and an accurate dosage of 2000 IU. Fetal growth progress was observed for 14 days. Results: Fetal weight was higher at the beginning, after 1 and 2 weeks of observation in the optimal vit. D group compared with the suboptimal group. The analysis was adjusted to the mother’s age, gestational week, and the number of pregnancies. Conclusions: Greater fetal weight gain can be observed in women with FGR (fetal growth restriction) who intake vitamin D at the recommended dose of 2000 IU compared with women with FGR and with a vitamin D intake dosage lower than 500 IU.